Liquid-Liquid Microextraction with Vortex-Assisted for Determination of Palladium and Gold in Water Samples by Flame Atomic Absorption Spectrometry - Zhao, Jiao; Meng, Lifen; Xi Cheng, Jia; Yang, Yaling (Asian Journal of Chemistry, 2014)
In this research, a novel method is described for the determination of traces of palladium and gold in water samples by vortex-assisted liquid-liquid microextraction (VA-LLME) prior to flame atomic absorption spectrometry (FAAS) analysis. Palladium and gold reacted with diethyldithiocarbamate (DDTC) forming hydrophobic chelates (M-DDTC), which were extracted efficiently into pelargonic acid after vortex-mixing and centrifuging. The effects of experimental conditions concerning pH of sample solution, concentration of chelating agent, types and concentration of extraction solvent and emulsifying strength were evaluated and optimized. Under the optimal conditions, the calibration graph are linear in the range of 10-500 μg L-1, with the correlation coefficients (r2) more than 0.9950. The low limits of detection for palladium and gold were 2.4 and 1.6 μg L-1, respectively. The recoveries ranged from 96.77 to 97.18 % and the relative standard deviations (RSD) were between 0.7 and 1.8 % (n = 6). The method was successfully applied to the analysis of palladium and gold in water samples.